Effects of Compost on Nematode Pratylenchus sp. (Tylenchida: Pratylenchidae) Population in Patchouli - Subarjah, Cecep; Himawan, Toto; Puspitarini, Retno Dyah (Journal of Tropical Life Science, 2016)
Patchouli is seen as one of the most important export commodities in Indonesia. The presence of parasitic nematode Pratylenchus sp. creates a barrier to plant cultivation. Increasing organic content in soil by applying compost in the plantation is one of approaches in controlling the nematode. This research was mainly aimed to study the effects of compost fertilization on the population growth of nematode Pratylenchus sp. and yields on patchouli. These research used a Completely Randomised Design (CRD) consisting of 12 treatments with three replicates. Selected plant was inoculated with nematodes with the following initial population: 100, 200, 300, 400, and 500 nematodes in soil with and without compost. The plant with no inoculation was used as control. The result of the research confirmed that the addition of compost was capable of suppressing the population of nematode Pratylenchus sp. as much as 58.93 - 67.31% and 40.74 - 59.19% in root and in soil of each treatment, respectively. Compost applied in each treatment positively affected the increasing amount of Patchouli oil yielded, and it could also reduce the loss as much as 18.34 - 43.36%. Trichoderma sp. was found to be dominant in compost in the treatment with its population of 2.1 Ã— 104 propogul/g.